Copper-Catalyzed C–S Formation for the Synthesis of Benzyl Phenyl Sulfides from Dithiocarbamates - Zhou, Yu; Yang, Cheng-Li; Ye, Lei; Dong, Zhi-Bing (Synthesis, 2022)
An odorless and efficient protocol for the synthesis of benzyl phenyl sulfides is reported. Starting from environmentally friendly phenyl dithiocarbamates and commercially available benzyl halides as starting materials, the target compounds (benzyl phenyl sulfides) could be obtained smoothly and easily by using copper salt as catalyst and Cs2CO3 as base. This method features ligand/additive-free, the use of readily available starting materials, inexpensive catalysts, and good substrate suitability, illustrating its potentially synthetic value for the convenient preparation of some biologically active molecules.
Keywords: C–S coupling; dithiocarbamates; sulfide; synthesis; catalysis